Perancangan Desain Pengembangan Kemasan Keripik Singkong Mbak Sum Desa Ngawun Parengan Menggunakan Metode Kansei Engineering - Putri, Nidya Arindi; Kalista, Anggia; Wibowo, Moh. Muhyidin Agus; Anggraini, Susanti Dhini (Universitas PGRI Ronggolawe, 2024)
Industry in Indonesia has experienced a lot of progress, one of which is driven by policies in the small industrial sectors. The case study in this research is the